1997
DOI: 10.1029/97wr01616
|View full text |Cite
|
Sign up to set email alerts
|

Methods for predicting peak discharge of floods caused by failure of natural and constructed earthen dams

Abstract: that may be poorly known, especially for natural dams. We will show that the essential kinematics of breach formation and hydraulics of flow through a breach can be summarized in a physical model that leads to a computationally simple, essentially graphical method of predicting peak discharge from breaching of an earthen dam. Our method "predicts" peak discharges that agree well with observational data from past dam failures and involves no arbitrarily adjustable parameters.The remainder of this paper is organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
233
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(237 citation statements)
references
References 19 publications
4
233
0
Order By: Relevance
“…PGA thresholds for the triggering of mass movements in different areas show a large scatter. The threshold of 0.7 m s −2 found out by Wang et al (2010) for the Wenchuan 2008 earthquake relates to the extremely landslide-prone slopes of that area and is not applicable to the southwestern Pamir. Murphy et al (2002) suggested thresholds between 4.5 and 20.4 m s −2 for the rocky slopes of the Tachia Valley in Taiwan.…”
Section: Susceptibility To Lake Outburst Triggered By External Forcesmentioning
confidence: 99%
“…PGA thresholds for the triggering of mass movements in different areas show a large scatter. The threshold of 0.7 m s −2 found out by Wang et al (2010) for the Wenchuan 2008 earthquake relates to the extremely landslide-prone slopes of that area and is not applicable to the southwestern Pamir. Murphy et al (2002) suggested thresholds between 4.5 and 20.4 m s −2 for the rocky slopes of the Tachia Valley in Taiwan.…”
Section: Susceptibility To Lake Outburst Triggered By External Forcesmentioning
confidence: 99%
“…Obviously, the erosion process affects the breach development and the associated outflow rate. To predict key breaching parameters of a landslide dam (i.e., peak outflow rate and failure time), several studies have been performed (Costa, 1985;Evans, 1986;Walder and O'Connor, 1997;Jakob and Jordan, 2001) through statistical analysis of historic data. Several physically-based breach models for embankment dams have also been developed (i.e., DAMBRK -Fread, 1977;BREACH -Fread, 1988;BEED -Singh and Quiroga, 1987;HR-BREACH -Mohamed, 2002;SIMBA -Temple et al, 2005;Hanson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This estimate is based on the following considerations. The observed discharge rate of natural dams with an initial hydraulic head of <20 m during breaching is typically below 2,000 m 3 s −1 (Walder and O'Connor 1997). The flow rate, however, after breaching a dam near Khadinyar would have been moderated by the hydraulic conditions in the Jhelum valley above the dam, that we assume were similar to those that exist at present.…”
Section: Unblocking the Dammentioning
confidence: 85%